Public health involvement in alcohol licensing decisions in the UK: a systematic review of qualitative studies - Elizabeth Goyder; Mark Clowes; Lindsay Blank; Emma Hock; Marie Rogerson (BMJ Publishing Group, 2024)
Introduction One approach to reducing alcohol consumption and related harm is to limit physical availability. However, a recent review found alcohol licensing decisions are not consistently associated with improved local health outcomes in the UK, despite public health teams (PHTs) having a statutory role in licensing. This may be explained by limitations in regulatory powers, or because PHTs have been unable to sufficiently influence the use of regulation. This review aims to synthesise qualitative evidence to understand the nature, barriers and enablers, and value of PHT involvement in alcohol licensing decisions in the UK.Methods A systematic review of qualitative evidence was conducted. Five electronic databases were searched, supplemented by web searches for grey literature and author, reference and citation searches for included studies. Data was extracted and quality assessed using the Critical Appraisal Skills Programme (CASP) checklist. Data was synthesised using thematic synthesis, and confidence in the findings was judged using the Confidence in Evidence from Reviews of Qualitative research (CERQual) approach.Results 10 reports, relating to four separate studies, met the eligibility criteria. Thematic synthesis generated seven analytical themes. We found variation in how PHTs' role in licensing is understood and enacted, with shared barriers and enablers. PHTs are often not regarded as a key consultee, though some teams found success in pursuing a more strategic approach. While the public health licensing objective in Scotland is considered an asset, it does not guarantee influence. Regardless of its presence, there is variation in the perceived value of PHTs' involvement in licensing.Conclusions A more strategic focus may be of value to PHTs and help strengthen their impact on licensing. However, given the limited potential for public health benefits through influencing regulatory decision-making, PHTs may want to consider if it is the most effective use of limited resource in tackling alcohol-related harms.PROSPERO registration number CRD42023452508.